PENGGUNAAN MEDIA PAPAN LUKIS KARAKTER KARTUN UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII-6 SMP NEGERI 42 BEKASI: Penelitian Tindakan di Kelas VIII-6 SMP Negeri 42 Bekasi Tahun Ajaran 2018/2019 - Fitri Tyas Sari; Safitri, Desy; Saipiatuddin (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2020)
The main purpose of this research is to know does the use of cartoon character art board as a media could could be increasing the Score and activeness the Social Studies learning result of 41 students in the class of VIII-6, SMP Negeri 42 Bekasi, 2nd semester, education year of 2018/2019. This research was done from March to May 2019. The applied method in this research is Classroom Action Research (PTK) Method. which was done by a collaboration with social science teachers at SMP Negeri 42 Bekasi. 3 stages was applied during the research, they were: Planning, Acting, Observing and Reflecting. This research found the increase of learning result in every stage that was applied. In the 1st stage, there were 51% (21 students) who had score for learning result above the minimum standardize score which is 75. 2nd stage found there were 73% (30 students) who had score for learning result above the minimum standardize score which is 75. And in the 3rd stage, there were 85% (35 students) who had score for learning result above the minimum standardize score which is 75. Moreover, cartoon character art board media able to increase students’ activity to learn as well. Active level percentage in the first cycle was 12%. In the second cycle was increasing to 38%. And in the third cycle significantly increased to 54%. The conclusion of the research is the using of cartoon character art board as a media could increase the Social Studies learning result and the active level of the students, therefor the students could get a better score for social studies subject which is above the minimum standardize score 75.